Spatio-Temporal Changes of Aridity in the Province of Naâma (Western Algeria) - Miloud Oubadi; Mohammed Faci (Annals of Arid Zone, 2024)
Arid regions are characterized by the fragility of their ecosystems, which are highly vulnerable to climate change. The increase in aridity in these regions makes them more exposed to droughts. This article analyses the trend in aridity and the expansion of drylands in the Wilaya (province) of Naâma, which is an arid region in south-western Algeria, over the period of 1951 to 2020. Monthly rainfall data from the Global Precipitation Climatology Centre (GPCC), as well as monthly mean temperature and potential evapotranspiration (PET) data from the Climatic Research Unit (CRU), characterized by a spatial resolution in grid points of 0.5º, were used. The results showed an increase in annual aridity, leading to transformation of drylands in to arid lands. As a result of these changes an additional 10% area of semi-arid land to converted to arid zone